2010
DOI: 10.1038/nprot.2009.243
|View full text |Cite
|
Sign up to set email alerts
|

Experimental acute biliary pancreatitis induced by retrograde infusion of bile acids into the mouse pancreatic duct

Abstract: Mechanistic studies of acute pancreatitis require animal models because clinical material is generally not available during the early phases of the disease. Here we describe a protocol to induce biliary pancreatitis by retrogradely infusing bile acids into the pancreatic duct of anesthetized mice. The resulting model replicates events believed to be responsible for the onset of clinical biliary (i.e., gallstone) pancreatitis and creates highly reproducible pancreatitis with a severity that depends on the conce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
79
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 97 publications
(87 citation statements)
references
References 9 publications
3
79
0
Order By: Relevance
“…It should be noted that 2-APB is also an inhibitor of SOCE. To evaluate whether our findings with RyR inhibitors on TLCS responses in isolated acinar cells are relevant in vivo, we employed our recently published pancreatitis model in which TLCS is briefly infused in the PD of anesthetized mice (39). This results in inflammation and necrosis of the pancreatic head that is maximal after 24 h (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It should be noted that 2-APB is also an inhibitor of SOCE. To evaluate whether our findings with RyR inhibitors on TLCS responses in isolated acinar cells are relevant in vivo, we employed our recently published pancreatitis model in which TLCS is briefly infused in the PD of anesthetized mice (39). This results in inflammation and necrosis of the pancreatic head that is maximal after 24 h (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Pancreatitis was induced by retrograde infusion of the bile acid TLCS (3 mM) or taurocholic acid (TC, 37 mM) in the distal common bile duct and pancreatic duct, as recently described (39). Briefly, C57BL/6 mice between 8 and 12 wk (20 -25 g) were anesthetized with a ketamine (120 mg/kg)-xylazine (12 mg/kg) mixture (Butler Schein, Chicago, IL).…”
Section: Detection and Analysis Of Cellular Camentioning
confidence: 99%
“…Intraductal Bile Acid Infusion Model of Pancreatitis-Pancreatitis was induced by retrograde infusion of the bile acid TLCS (3 mM) or taurocholate (TC) (37 mM) dissolved in saline into the distal common bile duct and pancreatic duct, as recently described (27). Briefly, mice between 8 and 12 weeks (20 -25 g) were anesthetized with a ketamine (120 mg/kg)/xylazine (12 mg/kg) mixture (Butler Schein, Chicago, IL).…”
Section: Methodsmentioning
confidence: 99%
“…One of the most accepted theories is that bile reflux into the pancreatic ductal system leads to AP. We know from animal studies, that retrograde infusion of bile acids into the pancreatic duct triggers pancreatitis [3,64,65]. Therefore the cytotoxic effects of bile acids have been widely investigated in the pancreas [66][67][68][69] [68,74].…”
Section: Pancreasmentioning
confidence: 99%
“…Numerous studies indicated that bile reflux into the pancreas may lead to pancreatic injury and as a result can induce AP [63][64][65]. Therefore, a better understanding of the mechanisms underlying bile-induced pancreatic injury and its prevention may provide novel therapeutic tools for the treatment of AP.…”
Section: Effect Of Bile Acids On Pancreatic Ductal Cellsmentioning
confidence: 99%